2017
DOI: 10.1080/09688080.2017.1392220
|View full text |Cite
|
Sign up to set email alerts
|

“Without this program, women can lose their lives”: migrant women’s experiences with the Safe Abortion Referral Programme in Chiang Mai, Thailand

Abstract: For displaced and migrant women in northern Thailand, access to health care is often limited, unwanted pregnancy is common, and unsafe abortion is a major contributor to maternal death and disability. Based on a pilot project and situational analysis research, in 2015 a multinational team introduced the Safe Abortion Referral Programme (SARP) in Chiang Mai, Thailand, to reduce the socio-linguistic, economic, documentation, and transportation barriers women from Burma face in accessing safe and legal abortion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(53 citation statements)
references
References 20 publications
0
53
0
Order By: Relevance
“…Not all of these women can access legal services on their own and some go to informal providers on either side of the border with or without the help of friends [ 88 ]. Burmese migrants also need their friends to navigate the complex and unfamiliar Thai system of legal abortion [ 89 , 90 ]. Similarly, in a study of 17 Mexican women who crossed the border to use legal abortion services in California, the women reported learning about the clinic from family members, friends, or the Internet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all of these women can access legal services on their own and some go to informal providers on either side of the border with or without the help of friends [ 88 ]. Burmese migrants also need their friends to navigate the complex and unfamiliar Thai system of legal abortion [ 89 , 90 ]. Similarly, in a study of 17 Mexican women who crossed the border to use legal abortion services in California, the women reported learning about the clinic from family members, friends, or the Internet.…”
Section: Resultsmentioning
confidence: 99%
“…Gipson [87] Cambodia Petitet [21] Burma/Thaïland Arnott [88], Tousaw [89], Tousaw [90] Middle East Iran Zamanian [36] Saudi Arabia Alsibiani [49] Palestinian OT Shahawy [98] through the abortion process alone (only one mentions having told her parents) [26].…”
Section: Philippinementioning
confidence: 99%
“…Most articles referred to legal restrictions as one of the main barriers to access ToP, and the main reason why humanitarian organisations may opt not to offer ToP under any circumstances in humanitarian contexts (5,23,24,(27)(28)(29)(30)(31)(32)(33)(34)(35). Among other reasons, restrictive abortion laws (23,24,29,30,34,35), i.e.…”
Section: Legal Environmentmentioning
confidence: 99%
“…44 Culture/context appropriate Interventions that were specific to the context and the culture were seen to be more beneficial and as effective even for interventions that were are legally restricted such as abortions. 45 A study by Wayte et al 46 also found it was necessary to modify guidelines to the local context. Meeting with religious and community leaders were important for building trust and for getting permission to initiate certain interventions that may be innovations, such as CHWs delivering injectable contraceptives, 15 or introducing programming for adolescent girls.…”
Section: Chws Involvement/outreach Workersmentioning
confidence: 99%